2011
DOI: 10.1038/sj.bjc.6606058
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of human AP endonuclease inhibitors in melanoma and glioma cell lines

Abstract: Aims:Modulation of DNA base excision repair (BER) has the potential to enhance response to chemotherapy and improve outcomes in tumours such as melanoma and glioma. APE1, a critical protein in BER that processes potentially cytotoxic abasic sites (AP sites), is a promising new target in cancer. In the current study, we aimed to develop small molecule inhibitors of APE1 for cancer therapy.Methods:An industry-standard high throughput virtual screening strategy was adopted. The Sybyl8.0 (Tripos, St Louis, MO, USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 45 publications
(66 reference statements)
1
65
1
Order By: Relevance
“…The ''low affinity'' attribute may stem from the fact that small molecules are unable to replicate the ''high affinity'' binding contacts seen in the APE1/AP-DNA complex, which spans roughly 7-8 bp in length. Indeed, in an extensive structure-function activity relationship study, the introduced modifications only slightly increased the effectiveness of the analogs against (7,131,142,167), confirming that the nuclease function(s) of the protein plays a critical role in repairing alkylative DNA damage, presumably abasic sites. Future studies will need to examine the utility of the most promising compounds in both combinatorial and synthetic lethal treatment paradigms, and may need to employ covalently linked, small molecules that bind simultaneously multiple functional sites of APE1.…”
Section: Small-molecule Inhibitorsmentioning
confidence: 83%
See 1 more Smart Citation
“…The ''low affinity'' attribute may stem from the fact that small molecules are unable to replicate the ''high affinity'' binding contacts seen in the APE1/AP-DNA complex, which spans roughly 7-8 bp in length. Indeed, in an extensive structure-function activity relationship study, the introduced modifications only slightly increased the effectiveness of the analogs against (7,131,142,167), confirming that the nuclease function(s) of the protein plays a critical role in repairing alkylative DNA damage, presumably abasic sites. Future studies will need to examine the utility of the most promising compounds in both combinatorial and synthetic lethal treatment paradigms, and may need to employ covalently linked, small molecules that bind simultaneously multiple functional sites of APE1.…”
Section: Small-molecule Inhibitorsmentioning
confidence: 83%
“…Some of the earliest work, published by Kelley and colleagues, revealed that APE1 provides resistance against not only MMS and hydrogen peroxide, but also the anti-cancer agents thiotepa, etoposide, and ionizing radiation (221). Through the efforts of many labs since, there is a general consensus emerging that indicates a role for APE1 in dictating cellular responsiveness to clinically relevant alkylators, most notably temozolomide (7,14,137,142,193), and a subset of chain-terminating nucleoside analogs, most prominently troxacitabine (114,137,180). Such a role is consistent with the biochemical activities of APE1, as alkylating agents, particularly mono-functional versions, induce a high number of abasic sites through both direct and indirect mechanisms, and certain anti-metabolites generate exonuclease 3¢-end substrates.…”
Section: Protein Depletionmentioning
confidence: 99%
“…Interestingly, the inhibitory effect was significantly increased in the Asp148Glu APE1 polymorph, previously implicated in cancer predisposition (see Section 5.4. APE1 polymorphisms and cancer susceptibility) (Mohammed et al 2011). A number of other groups have been working on the development of APE1 DNA repair inhibitors.…”
Section: Ape1 Dna Repair Domain Inhibitorsmentioning
confidence: 99%
“…5 An alternative approach has utilised knowledge of the crystal structure of the APE1 active site to strategically design inhibitor templates that are applied in a virtual screen of much larger compound libraries. 6 Using these strategies, a number of potential inhibitors have been identified and are currently undergoing preclinical evaluation.…”
Section: Apurinic/apyrimidinic Endonuclease As a New Ber Targetmentioning
confidence: 99%